Systemic Financial Distress and Auction-Based Bankruptcy Reorganization - Hausch, Donald B.; Ramachandran, S. (2012)
Most bankruptcy procedures try to reorganize a financially-distressed firm's debts to a serviceable level through negotiations overseen by courts. Markets are an alternative to such negotiations. This paper develops a market-based approach that is appropriate if claimants are severely cash-constrained and there is merit in having existing owners-managers remain in control. This approach was developed in response to the 1997 Asian Crisis, where the sheer numbers of over-indebted firms, creditors with poor incentives, and inexperienced courts stymied negotiated resolution. The scheme, however, can be applied to other crisis settings that exhibit particular characteristics. One such setting could be the resolution of external sovereign debts, a situation where creditors obviously cannot take possession of a country. The scheme arranges creditors in a queue to be serviced in sequence from the firm's operating cash flows. Creditors bid for their position in this queue, and those accepting a greater proportionate reduction in the face value of their claims are placed ahead of the others. Any existing hierarchy of claims is honored by having claimants bid for their positions within the relevant segment of the queue. No one in the queue (including owners who are last) is paid anything until the (reduced) debts of the first in line are fully discharged using the firm's operating cash surpluses. The queue then moves up and the next claimant in line is serviced. The paper shows that, in equilibrium, the aggregate debts of the firm are reduced enough to provide a positive expected residual return to the owner-managers, which improves their incentives to efficiently operate the firm and can result in an outcome that is Pareto superior to other bankruptcy procedures. We discuss the efficiency properties of this scheme and its appropriateness to situations of systemic financial distress.